Long-Term Quercetin Dietary Enrichment Partially Protects Dystrophic Skeletal Muscle - Spaulding, Hannah R. (PLoS One, 2016)
Duchenne muscular dystrophy (DMD) results from a genetic lesion in the dystrophin gene and leads to progressive muscle damage. PGC-1α pathway activation improves muscle function and decreases histopathological injury. We hypothesized that mild disease found in the limb muscles of mdx mice may be responsive to quercetin-mediated protection of dystrophic muscle via PGC-1α pathway activation. To test this hypothesis muscle function was measured in the soleus and EDL from 14 month old C57, mdx, and mdx mice treated with quercetin (mdxQ; 0.2% dietary enrichment) for 12 months. Quercetin reversed 50% of disease-related losses in specific tension and partially preserved fatigue resistance in the soleus. Specific tension and resistance to contraction-induced injury in the EDL were not protected by quercetin. Given some functional gain in the soleus it was probed with histological and biochemical approaches, however, in dystrophic muscle histopathological outcomes were not improved by quercetin and suppressed PGC-1α pathway activation was not increased. Similar to results in the diaphragm from these mice, these data suggest that the benefits conferred to dystrophic muscle following 12 months of quercetin enrichment were underwhelming. Spontaneous activity at the end of the treatment period was greater in mdxQ compared to mdx indicating that quercetin fed mice were more active in addition to engaging in more vigorous activity. Hence, modest preservation of muscle function (specific tension) and elevated spontaneous physical activity largely in the absence of tissue damage in mdxQ suggests dietary quercetin may mediate protection.